Stress concentration factors in steel tubular KT-connections with FRP-Wrapping under bending moments. (October 2021) - Zavvar, Esmaeil; Sadat Hosseini, Alireza; Lotfollahi-Yaghin, Mohammad Ali
Abstract: Stress concentration factors (SCF) in steel tubular joints have gained considerable attention since it is the crucial parameter for fatigue design of steel tubular structures. Meanwhile, among various strengthening methods, Fiber Reinforced Polymer (FRP) wrapping has shown to be an effective scheme for reinforcing steel structures. This study is dedicated to the numerical investigation of SCF values in FRP-strengthened tubular KT-joints under the action of In-Plane Bending (IPB) and Out-of-Plane Bending (OPB) moments on the central as well as outer braces with three various practical loading patterns per each moment. The Finite Element (FE) modeling methodology for joint geometry and FRP generation was validated against the available data in the literature and well-known codes. The effects of different geometrical parameters along with the FRP parameters on the SCF values were studied through post-analyzing a total of 2920 FE models. The numerical parametric studies indicated that FRP strengthening could lower the SCF values in KT-connections by about 30 and 55 percent under IPB and OPB moments, respectively. Using the driven data, practical fatigue design formulas were developed for predicting SCF in FRP-strengthened KT-joints under bending moments, and reliability of the proposed equations was examined using Fatigue Guidance Review Panel recommendations.